A CASE STUDY ON THE INTEGRATION OF ISLAMIC VALUES IN LEARNING AT SDIT QURRATA A’YUN - Efendi, Didik; Rahmawati, Rahmawati (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Education not only develops cognitive, affective, and psychomotor aspects, but also instills faith, piety, and noble character in accordance with the mandate of the 1945 Constitution. Learning practices in elementary schools often still focus on general subjects, while Integrated Islamic Elementary Schools (SDIT) integrate academic and spiritual dimensions through an TERPADU approach (Telaah, Eksplorasi, Rumuskan, Presentasikan, Aplikasikan, Duniawi, Ukhrawi). Objective: This study aims to describe the strategies used by teachers to internalize Islamic values in general subjects at SDIT Qurrata A'yun Abepura. Method: This research uses a qualitative case study approach. The research subjects are teachers and students of SDIT Qurrata A'yun. Data were collected through observation, in-depth interviews, and document analysis, then analyzed through reduction, presentation, and conclusion drawing. Research results: The integration of Islamic values was carried out systematically through planning, implementation, and evaluation. Teachers used an TERPADU approach in every learning activity, while evaluation was carried out through teacher briefings and meetings with parents. The main challenge was the lack of competence among teachers who did not have a deep understanding of Islamic values. Conclusion: The strategy of internalizing Islamic values through the TERPADU approach effectively strengthens the integration of spiritual values in general learning, creating synergy between students' knowledge and character. These findings can serve as a model for other Islamic schools and provide recommendations for policymakers to formulate national guidelines for the integration of Islamic values across all subjects at the elementary/Madrasah Ibtidaiyah level.